Teacher Professional Development in Implementing Inclusive Education Practices - Paulus Robert Tuerah (PT. NALURI EDUKASI PRESS, 2025)
This study aimed to examine teacher professional development approaches for implementing inclusive education practices, identifying barriers, facilitators, and effective models that support successful program implementation and sustainable classroom practice changes. A qualitative systematic literature review was conducted, analyzing peer-reviewed research published between 2015-2024 from major educational databases. The review employed thematic analysis to identify recurring patterns across studies examining professional development effectiveness in inclusive education contexts. Quality assessment criteria ensured inclusion of rigorous, relevant studies that contributed to evidence-based understanding of effective professional development practices. The analysis revealed three major themes: significant barriers including systemic resource constraints, negative teacher attitudes, and organizational culture challenges; key facilitators comprising strong leadership support, collaborative learning structures, high-quality content, and ongoing coaching; and effective models featuring collaborative consultation, professional learning communities, mentoring approaches, and technology-enhanced delivery methods. Findings indicated that successful professional development requires comprehensive, sustained approaches addressing multiple organizational levels simultaneously. Traditional one-time training events proved insufficient for promoting the complex changes required for inclusive education implementation. The most effective programs combined theoretical knowledge with practical application opportunities, peer collaboration, and ongoing support systems that honor adult learning principles while facilitating transformative changes in teacher beliefs and practices.